In-Vitro Investigation of the Shear Bond Strength of Different Orthodontic Adhesives to Enamel - Huda Abutayyem (Wolters Kluwer Medknow Publications, 2024)
Background: The shear bond strength (SBS) of orthodontic adhesives to enamel is a critical factor in the success of orthodontic treatment. Various adhesives are available in the market, each with different trade names and claimed properties that could influence their bond strength. Understanding these differences is essential for clinical decision-making. Materials and Methods: In this in-vitro study, 60 freshly extracted human premolars were collected and randomly divided into four groups: Group A (Adhesive X-Trade Name: BondPlus), Group B (Adhesive Y-Trade Name: OrthoBond), Group C (Adhesive Z-Trade Name: PowerBond), and Group D (Control). The enamel surfaces were cleaned, polished, and etched following standard protocols. Orthodontic brackets were bonded to the teeth using the respective adhesives according to the manufacturer's instructions. A universal testing machine was employed to measure the SBS, and the data were analyzed using ANOVA with post-hoc tests. Results: The mean SBS values (MPa) were as follows: Group A = 15.2, Group B = 14.8, Group C = 16.5, and Group D (Control) =10.3. Statistical analysis revealed significant differences among the groups (P < 0.05). Post-hoc tests indicated that Group C exhibited significantly higher SBS compared to the other groups. Conclusion: Our findings suggest that among the orthodontic adhesives tested, PowerBond demonstrated superior shear bond strength to the enamel. However, further research is warranted to explore other aspects of adhesive performance and clinical implications.